The Influence Of Knowledge Economy And Culture On Economic Resilience And Sustainable Development In Indonesia - Nizar, Nefo Indra; Nazir, Ahmad; Sholeh, Achmad Nur (Doctoral Program of Social Science Pasundan University, 2024)
The purpose of this study is to find out whether the knowledge economy and culture are able to overcome the problems of economic resilience and sustainable development in Indonesia. The knowledge economy is a knowledge-based development built on a knowledge framework, while the cultural economy is based on a cultural economy framework. Economic resilience is needed so that sustainable development can run well. Economic resilience is able to maintain economic growth while strengthening sustainable development with the procedures of the knowledge economy and cultural economy. The research method uses Generalized Least Square regression estimation to measure the influence of knowledge economy and culture variables on economic resilience and sustainable development in Indonesia. From the results of the study, the variables of the knowledge economy and culture have a positive and significant effect on economic resilience and sustainable development in Indonesia. This study includes the variables of education, technology, innovation, aspects of democracy, and cultural heritage as proxies for the knowledge economy and culture. Sustainable development requires sustainable economic resilience in addition to the knowledge economy and culture. Sustainable economic resilience through technology and innovation will be able to survive and develop again so that sustainable development can continue to run and overcome shocks that will always appear in the economic cycle. The addition of determinants of innovation, cultural economy and sustainable development in Indonesia can strengthen the economic resilience variables and complement economic resilience to be better and unique.